Pelatihan Pembuatan Masker Wajah Organik Kelompok Ibu PKK di Desa Sukabanjar Pesawaran - Ulandari, Atri Sri; Pardilawati, Citra Yuliyanda; Yuningrum, Hesti; Yunianto, Andi Eka; Putri, Zakiah Meyra; Nurlaili, Nurlaili (Pakis Journal Institute, 2025)
Community Service was carried out to provide education and training on making natural face masks from medicinal plants in Sukabanjar Village, Pesawaran. The purpose of this activity is to provide information to the community regarding how to make natural face masks using natural ingredients available in the area as an effort to maintain healthy facial skin. The method applied is to provide counseling on the benefits of medicinal plants as well as providing booklets and training on making natural face masks from medicinal plants in the local environment. The specific targets to be achieved are to improve the ability to process natural ingredients into traditional cosmetic preparations and motivate the community, especially members of the PKK women’s group in Sukabanjar Village to always maintain healthy facial skin. With this training program, it is expected that the community, particularly members of the PKK women’s group in Sukabanjar Village, can utilize local medicinal plants as ingredients to make natural cosmetics without chemical mixtures that can provide many benefits for daily use.